TRANSFORMING INNOVATION INTO ENTERPRISE: A PATHWAY FOR SUSTAINABLE COMMERCIALIZATION IN NIGERIA’S TECH ECOSYSTEM - Yusuf Usman (My University, 2025)
Innovation remains a key driver of national development, yet the transformation of creative ideas into commercially viable enterprises continues to challenge Nigeria’s technology ecosystem. Despite numerous research outputs, startups, and government initiatives, the pathway from innovation to enterprise remains poorly defined. This paper examines the barriers impeding sustainable commercialization and proposes a structured model to link innovators, investors, policymakers, and markets. The study employs a synthesis of literature, secondary data, and contextual analysis to identify existing gaps and potential enablers. It highlights the need for improved innovation infrastructure, accessible financing mechanisms, and a unified commercialization framework tailored to Nigeria’s socio-economic realities. The paper concludes by proposing an ecosystem- based commercialization model that can drive inclusive and sustainable technology- driven growth in Nigeria.